Pengaruh Fortifikasi Zat Besi terhadap Sifat Kimia dan Sensori Biskuit Ubi Kayu yang Disuplementasi Tepung Ikan-Tempe - Retno Setyawati; Nur Aini; Hidayah Dwiyanti (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
The prevalence of anemia in pregnant women in Indonesia in 2013 was still high at 37.1%. The impact of anemia on long-term pregnant women causes a decrease in the quality of human resources. Therefore, it is necessary to provide foods with high iron content and which are easily absorbed. Cassava biscuits that have been enriched with Tempe fish flour and fortified Fe are expected to be an alternative to anemia control and pregnant women PEM through a